Visualisasi Jaringan Penelitian Teacher Efficacy Menggunakan Bibliometrik dan VOSviewer - Wahid Muhsin; Diding Nurdin; Nani Hartini (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2020)
Abstract: This study aims to visualize the research landscape on teacher efficacy and its moderating variables over the last five years using bibliometric analysis and VOSviewer mapping. The growing number of studies on teacher efficacy especially in relation to leadership, organizational support, digital competence, and pedagogical transformation requires a systematic synthesis to understand publication trends, thematic structures, and collaborative research networks. Data were collected from the Scopus database using the keywords “teacher efficacy” AND “moderation,” and then refined through a selection process to ensure relevance and completeness. Bibliometric techniques and science mapping were employed to examine publication distribution, author productivity, country contributions, and keyword co- occurrence. VOSviewer was used to generate visual clusters that illustrate the intellectual structure of the field. The findings show that teacher efficacy consistently emerges as a central theme connecting digital competencies, psychological well-being, instructional leadership, and professional development. Indonesia appears as one of the most productive countries, indicating strong research momentum driven by curriculum reforms and digital transformation in education. Keyword mapping reveals two major thematic clusters: one focusing on technological and psychological aspects, and the other on professional learning and pedagogical models. Overall, the study concludes that teacher efficacy functions as a pivotal construct in educational research, bridging technological, organizational, and pedagogical dimensions. The results provide a comprehensive overview of the field and highlight research gaps that can inform future studies on teacher efficacy and moderating variables. Keywords: teacher efficacy, moderation; bibliometric analysis, VOSviewer, digital competence. Abstrak: Penelitian ini bertujuan memvisualisasikan lanskap penelitian mengenai teacher efficacy dan variabel moderasinya dalam lima tahun terakhir melalui analisis bibliometrik dan pemetaan VOSviewer. Meningkatnya jumlah publikasi terkait teacher efficacy khususnya yang berkaitan dengan kepemimpinan, dukungan organisasi, kompetensi digital, serta transformasi pedagogis menunjukkan perlunya sintesis sistematis untuk memahami tren publikasi, struktur tematik, dan jaringan kolaborasi ilmiah. Data diperoleh dari basis data Scopus dengan kata kunci “teacher efficacy” AND “moderation,” kemudian diseleksi untuk menjamin relevansi dan kelengkapan metadata. Teknik bibliometrik dan science mapping digunakan untuk menganalisis distribusi publikasi, produktivitas penulis, kontribusi negara, serta ko-okurensi kata kunci. VOSviewer dimanfaatkan untuk menghasilkan visualisasi klaster yang menggambarkan struktur intelektual bidang penelitian. Hasil penelitian menunjukkan bahwa teacher efficacy merupakan tema sentral yang menghubungkan kompetensi digital, kesejahteraan psikologis, kepemimpinan instruksional, dan pengembangan profesional. Indonesia muncul sebagai salah satu negara paling produktif, mencerminkan kuatnya dorongan penelitian seiring reformasi Kurikulum Merdeka dan digitalisasi pendidikan. Pemetaan kata kunci menunjukkan dua klaster utama: klaster yang berfokus pada aspek teknologi dan psikologis, serta klaster yang menyoroti pembelajaran profesional dan model pedagogis. Secara keseluruhan, penelitian ini menyimpulkan bahwa teacher efficacy berfungsi sebagai konstruksi kunci yang menjembatani dimensi teknologi, organisasi, dan pedagogi. Hasil penelitian memberikan gambaran komprehensif serta mengidentifikasi peluang penelitian masa depan terkait teacher efficacy dan variabel moderasi. Kata kunci: teacher efficacy, moderasi, analisis bibliometrik, VOSviewer, kompetensi digital